Identification of maximum loadability in power system with line outages using chaotic mutation immune evolutionary programming / Sharifah Azma Syed Mustaffa, Ismail Musirin and Muhammad Murtadha Othman - Syed Mustaff, Sharifah Azma; Musirin, Ismail; Othman, Muhammad Murtadha (UiTM Press, 2018)
Recently, the sudden rise of demand for electricity leads to the voltage instability in power system which consequently affects the maximum loadability of the system. Therefore, it is crucial to solve the voltage stability problem and keep the voltage profile within the limit. The presence of line outage contingency also affects the voltage stability of the system. This paper proposes a new algorithm namely Chaotic Mutation Immune Evolutionary Programming (CMIEP) for maximum loadability under N-1 contingency in a transmission system. The formulation of the contingency analysis and the constraints are initially presented. Next, the ranking process was performed based on the predeveloped voltage stability index termed as Fast Voltage Stability Index (FVSI) to identify the most critical line outage for the system during N-1 contingency. IEEE 30-bus Reliability Test System (RTS) was utilized to test the proposed technique. The obtained results show the effectiveness of the proposed optimization technique and successively able to compute maximum loadability of the optimal bus during N-1 contingency.